2021
DOI: 10.21203/rs.3.rs-151831/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction and Trend of Tactile Acuity, Pain and Disability in Acute LBP: A Six-Month Prospective Cohort Study

Abstract: Background: Chronic back pain is known to be associated with altered tactile acuity. Tactile acuity is measured using the Two-Point Discrimination (TPD) test in both clinical and research settings. In subjects with chronic low back pain, the TPD threshold (TPDT) is increased and is associated with persistent pain. It remains unknown, however, whether TPDT is also altered in cases of acute pain, or whether it could be used as a predictor of future pain and disability at an early stage of LBP.The main objective … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…For example, patients with CRPS 7 , or other types of chronic pain respond poorer with 2-point discrimination tasks 7 . Moreover, more recent studies have confirmed that such a tuning disruption already occurs in the acute phase of pain 25 or even immediately following noxious stimulus application 2 and preliminary data shows that intervention directed at spatial retuning may effectively reduce pain intensity 26,27 .…”
Section: Spatial Tuning In Acute and Chronic Painmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, patients with CRPS 7 , or other types of chronic pain respond poorer with 2-point discrimination tasks 7 . Moreover, more recent studies have confirmed that such a tuning disruption already occurs in the acute phase of pain 25 or even immediately following noxious stimulus application 2 and preliminary data shows that intervention directed at spatial retuning may effectively reduce pain intensity 26,27 .…”
Section: Spatial Tuning In Acute and Chronic Painmentioning
confidence: 95%
“…Moreover, more recent studies have confirmed that such a tuning disruption already occurs in the acute phase of pain 28 or even immediately following noxious stimulus application 2 and preliminary data shows that intervention directed at spatial retuning might be effective in pain reduction 30,31 .…”
Section: Spatial Tuning During Acute and Chronic Painmentioning
confidence: 95%